The Supply Side of the Digital Divide: Is There Equal Availability in the Broadband Internet Access Market? - James E. Prieger (University of California, Department of Economics, 2002)
The newest dimension of the Digital Divide is access to broadband (high-speed) Internet service. Using comprehensive U.S. data covering all forms of access technology (chiefly DSL and cable modem), I look for evidence of unequal broadband availability in areas with high concentrations of poor, minority, or rural households. There is little evidence of unequal availability based on income or on black or Hispanic concentration. There is mixed evidence concerning availability based on Native American or Asian concentration. Other findings: rural location decreases availability; market size, education, Spanish language use, commuting distance, and Bell presence increase availability.
Keywords: L96; J78; L51; 330; Internet; Breitbandkommunikation; Wohnstandort; Ethnische Gruppe; USA; Digitale Spaltung; Randgruppe